Aspectos psicosociales del cáncer de pulmón - Krikorian, Alicia; Bringas, Sara (Psicooncología, 2006)
Lung cancer is the cancer with the highest incidence and mortality rates in the world. Has a poor prognosis and most affected patients are in advance ages, becoming a more vulnerable population due to diffi culties in access to health resources and social support. Lung cancer produces multiple symptoms, both physical and psychological, which account for the decrease in quality of life. Depression and anxiety, as well as general distress rates are higher than those found in other oncologic entities and although research indicates the need for psychosocial support, assessment of psychosocial aspects is not a common practice and little attention is dedicated to psychological intervention. The present article exposes an extensive review of psychosocial aspects of lung cancer.